Liquid Thinking nspirational lessons from the world's great achievers - Hughes,Damian (London Capstone, 2009)
Stuck in a rut? Know what you want but don?t know how to get it? Feel like life is passing you by? Sick of getting mediocre results? Then enter the wonderful world of Liquid Thinking
Keywords: Inspiration